Los dilemas de un partido personalista en la reproducción de su vibrancia: caso de estudio partido político Centro Democrático (2020)
This research explores the dilemmas that arise in the reproduction of vibrancy in a personalist political party such as the Centro Democrático (CD). To this end, it examines why, despite the fact that the CD is a party that has the factors that reproduce vibrancy: trauma, purpose, channels of ambition and exit barriers (Rosenblatt, 2018), and is one of the organizations that generates the greatest affinity in the Colombian party system (31.4% of the total number of affiliates) (LAPOP, 2018), some facts in its organizational history show significant desertions, distancing and/or divisions and, therefore, a decrease in the levels of its vibrancy. The main argument suggests that, in spite of the presence of all the causal factors that stimulate high vibrancy, its configuration in different states/levels (more or less high), before the strong influence of a personalist leadership that promotes more ideological incentives by decreasing the access to material incentives; therefore, high vibrancy. To this effect, the main findings showed that the vibrancy in the CD is strongly sustained on ideological incentives and to a lesser extent on material incentives, generating easy desertion and division among party members. Linked to this phenomenon is the influence of the leadership of former ex President Alvaro Uribe, who has a positive influence on the cohesion of the militancy around trauma and purpose (ideological motivations) and, negatively, around adherence to clear rules of the game and exit barriers focused on a collective partisanship that transcends its own charisma (material motivations).